2022
DOI: 10.3389/fenvs.2022.936216
|View full text |Cite|
|
Sign up to set email alerts
|

Do environmental quality, financial inclusion, and good governance ensure the FDI sustainably in Belt and Road countries? Evidence from an application of CS-ARDL and NARDL

Abstract: Domestic capital adequacy and sustainable economic growth are heavily reliant on technological advancement, managerial know-how, and money supply in the economy. In this context, FDI has emerged and is placed at an apex position due to its unprecedented impact on achieving sustainability across the world. The motivation of this study is to scale the effects of good governance, financial inclusion, and environmental quality on inflows of FDI in BRI nations for the period from 1990 to 2020. Several panel econome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 148 publications
2
14
0
Order By: Relevance
“…Furthermore, studies have shown that a country's educational system may have a role in the kind of FDI it receives. Foreign direct investment (FDI) in “high-tech” sectors, for instance, is more likely to flow to nations with highly educated personnel, according to studies [ [85] , [86] , [87] , [88] ]. This is because of the complex skill sets essential to the success of these sorts of businesses.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies have shown that a country's educational system may have a role in the kind of FDI it receives. Foreign direct investment (FDI) in “high-tech” sectors, for instance, is more likely to flow to nations with highly educated personnel, according to studies [ [85] , [86] , [87] , [88] ]. This is because of the complex skill sets essential to the success of these sorts of businesses.…”
Section: Discussionmentioning
confidence: 99%
“…The study established that FDI has a catalyst role in the deterioration of environmental quality in both symmetric and asymmetric assessment, indicating the pollution haven hypothesis in attracting the continual inflows of FDI in the economy (70,82,(91)(92)(93)(94). Foreign direct investment (FDI) has been praised for its potential to spur economic growth and development.…”
Section: Long-run and Short-run Estimation: Symmetric And Asymmetric ...mentioning
confidence: 99%
“…The role of remittances on economic fundamentals such as poverty alleviation (32), reduction of inequality (33), financial development (34)(35)(36)(37), capital formation (38), employment (39), financial openness (40) and economic growth, household consumption(41) among other. Another line of empirical studies focusing on financial inclusion impacts poverty and inequality (42).…”
Section: Financial Inclusion and Remittancesmentioning
confidence: 99%